2019
DOI: 10.1016/j.ejvs.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Impact of Prosthetic Graft Replacement of the Ascending Aorta on Circumferential Strain in the Descending Aorta

Abstract: The results of this study demonstrate graft induced increases in circumferential deformation and distensibility in the native descending aorta in the presence of unchanged haemodynamics and stroke volume after proximal aortic graft replacement, suggesting that replacing native aorta with a graft increases pulse pressure and energy propagation downstream to the graft. This observation may have important clinical implications and may be a mechanism contributing to the reported risk of aneurysm formation or expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…One reason for aortic events after TAA replacement surgery may stem from biomechanical properties of grafts: Prosthetic grafts are stiffer than native aortic tissue and tubular in shape, thus providing a nidus for energy propagation to the distal aorta that increases stress on native tissue. Consistent with this, prior studies from our group using echocardiography showed that proximal grafts increase distal aortic wall excursions (strain) intra- 6 and post-operatively. 7 Our cardiac MRI (CMR) studies demonstrated further that proximal grafting produces short-term increases in both ascending and descending aortic flow velocity, flow-induced wall shear stress, and pressure-induced wall strain.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…One reason for aortic events after TAA replacement surgery may stem from biomechanical properties of grafts: Prosthetic grafts are stiffer than native aortic tissue and tubular in shape, thus providing a nidus for energy propagation to the distal aorta that increases stress on native tissue. Consistent with this, prior studies from our group using echocardiography showed that proximal grafts increase distal aortic wall excursions (strain) intra- 6 and post-operatively. 7 Our cardiac MRI (CMR) studies demonstrated further that proximal grafting produces short-term increases in both ascending and descending aortic flow velocity, flow-induced wall shear stress, and pressure-induced wall strain.…”
Section: Introductionsupporting
confidence: 84%
“…Whereas this is the first study that we are of aware of to examine ascending and descending aortic compliance patterns in patients long-term after proximal graft implantation, our findings add literature by our group and others demonstrating that differences in mechanical properties between current prosthetic grafts and the native aorta alter aortic wall biomechanics in regions distal to surgically treated territories. This premise is supported by both imaging 68 and computational modeling studies. 1315 In clinical studies, graft-induced changes in the distal aorta have been shown to be greatest in patients with genetically triggered TAA – in whom we 16 and others 1719 have shown aortic stiffness to be greatest.…”
Section: Discussionmentioning
confidence: 71%
“…Prosthetic grafts differ from the native aorta with respect to geometry and distensibility [9][10][11][12], and thus provide a stiff conduit to propagate high velocity flow into distal (non-grafted) segments. Consistent with this, prior studies by our group have shown ascending aortic grafts to acutely increase energy transmission to the native descending aorta, resulting in increased descending aortic distension as measured via intra-operative transesophageal echocardiography [13]. However, it remains uncertain whether such changes persist post-operatively in ambulatory patients (without modulatory effects of cardiac anesthesia), or whether magnitude of prosthetic graft-induced alterations in native aortic distension varies between patients with and without congenital or genetically associated aortopathies.…”
Section: Introductionsupporting
confidence: 80%
“…Rong et al ( 15 ) demonstrated amplification of circumferential strain in the descending thoracic aorta, paralleling distensibility by using intra-operative transoesophageal echocardiography to study the effect of endograft on the haemodynamic alteration. They showed that prosthetic replacement of the ascending aorta could interfere with the propagation of energy to the distal aorta resulting in adverse aortic remodelling.…”
Section: Pathophysiologymentioning
confidence: 99%